E-155 Higher prevalence of intraplaque hemorrhage in left carotid arteries than right. (4th August 2020) - Larson, A; Benson, J; Lanzino, G; Brinjikji, W
Abstract : Background: Ischemic stroke is more often diagnosed in the left hemisphere than the right. One prior study has found that there may be an asymmetrical prevalence of atherosclerosis with a higher prevalence of carotid artery disease on the left than the right. Methods: We sought to study the prevalence of carotid artery atherosclerosis and intraplaque hemorrhage in the right versus left carotid artery in a large population of patients. Results: Neck MRAs of 643 total patients were reviewed. Overall, there were similar degrees and distribution of degrees of stenosis. There was a higher prevalence of intraplaque hemorrhage in the left versus right carotid for all patients (P=0.02) and for symptomatic patients (P=0.002). This was not true for asymptomatic patients. There were no differences in the prevalence of plaque ulcer between right and left carotid arteries. Conclusions: In confirming a prior report, we found that left carotids are more likely to present with intraplaque hemorrhage as compared to right carotids. This was particularly true for patients with symptomatic manifestations including stroke, transient ischemic attack, amaurosis fugax and retinal artery occlusion. The reason underlying the increased prevalence of intraplaque hemorrhage in the left carotid artery remains enigmatic. Disclosures: A. Larson: None. J. Benson: None. G. Lanzino: None. W. Brinjikji: None.